Levantamento do meio físico e classificação de terras pelo Sistema de Capacidade de Uso do Solo no CCA/UFSCar - Lima, Maria Isabel de Oliveira (Universidade Federal de São Carlos, 2024)
Investigating the natural propensity for land use is extremely important, especially in environments subject to intense human action. When the soil's productive capacity conditions are not taken into account, and it is used inappropriately, underutilization or overutilization may occur, resulting in inefficiency or severe damage. From this perspective, the objective of the work was to determine the land use capacity at the Agricultural Sciences Center (CCA) of the Federal University of São Carlos (UFSCar), Araras campus. The potential of the land was assessed through information on the morphological, physical and chemical attributes of the soil made available in the CCA's detailed pedological survey, in addition to the ultra-detailed planialtimetric survey and field observations. The classification method adopted was the Land Use Capability System, which considers effective depth, texture, permeability, specific limiting factors, slope, erosion and current use, among others, in order to identify soils according to their greatest limitation. Based on the analyses, maps of current land use, land use potential and land use suitability were created. It was found that the entire area falls into Group A, whose intensity of use accommodates annual and perennial crops, pastures, reforestation and wildlife. There are, however, differences regarding soil conservation needs, verified between the classes present. On the campus there is a predominance of class III (94.14% of the total area of ​​classified land), indicating areas prone to complex conservation and/or improvement problems; in class II, with simpler problems, there is 2.31%; with the remainder (3.54%) presenting serious problems related to soil conservation. In addition to the 23.78% of the total area of ​​classified land occupied by Permanent Preservation Area (APP) and Legal Reserve (RL), in more than half of the area (67.59%) the land use is adequate to its capacity. There is usage above and below capacity at 3.54% and 5.09%, respectively. Regarding the sustainability of land use in the CCA/UFSCar, it is recommended for overused areas, currently under sugarcane cultivation, the adoption of less intensive soil management, depending on their limitations, or even the allocation of area for conservation, in addition to the implementation of recovery and erosion control practices. Underutilized soils, on the other hand, can be exploited to their maximum potential, which includes annual cultivation and more intensive management. For soils that are in their appropriate use, it is recommended the adoption and/or maintenance of conservation practices, due to the predominant use capacity class (III) on the campus, in order to guarantee sustainable management of the soil resource and the prevention of degradation of water resources.
Physical environment survey and land use classification by the Land Use Capability System at CCA/UFSCar
Keywords: Classificação interpretativa das terras; Conservação do solo; Manejo do solo; Pedologia; Lands interpretative classification; Soil conservation; Soil management; Pedology; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO